42. Multimodality intraoperative neurophysiologic monitoring in spondilotic myelopathy. Issue 1 (January 2015) - Giobbe, M.L.; Costa, P.
<x xml:space="preserve">Abstract</x> Cervico/dorsal spondilotyc myelopathy (CDSM) is the most frequent spinal disorder encountered in people aged >55 years. Although CDSM is frequently scheduled for multimodal intraoperative monitoring (MIOM), it is not completely clarified the rate of monitorability and intraoperative modification. We retrospectively reviewed the data from 361 consecutive spinal surgeries (213 CDSM, 35 intramedullary spinal cort tumors – IMSCT – and 113 extranedullary spinal cord tumors – EMSCT) in whom 4 lower limbs Motor Evoked Potentials (ll-MEPs) and posterior tibial nerve somatosensory evoked potential (ptn-SEPs) were studied. Patients were clinically classified according the MacKormick scale. The overall monitorability was 96.4% (IMSCT = 97.1%, EMSCT = 99.1%, CDSM = 94.8%). ptn-SEPs were absent or unilaterally present in 16.9% of the whole casistic (20% of IMSCT, 9.7% of EMSCT and 20.2% of CDSM); globally, ll-MEPs were absent or unilaterally recordable in 15.2% (11.4% of IMSCT, 4.4% of EMSCT and 21.6% of CDSM). The rate of postoperative worsening was higher in patients with T2 signal abnormality on preoperative MR images. Spondilotic myelopathy is the worst "scenario" for the intraoperative neurophysiologist.